Mesoporosity development in ZSM-5 zeolite upon optimized desilication conditions in alkaline medium - Groen, J.C; Peffer, L.A.A; Moulijn, J.A; Pérez-Ramı́rez, J (Colloids and surfaces. A, Physicochemical and engineering aspects, 2004)
The development of porosity in ZSM-5 zeolite by desilication in alkaline medium has been studied. Treatment of ZSM-5 in NaOH solutions leads to mesoporosity development, stemming from the preferential extraction of Si from the zeolite framework. Investigation of the influence of temperature and time during this treatment on the porous properties of the final material shows that the mesopore size and volume can be tuned to a certain extent by optimization of these two variables. Optimal treatment conditions lead to a spectacularly increased mesopore surface area (450%) from 40 m 2/g for the calcined zeolite to 225 m 2/g for the alkaline-treated material, while the micropore volume is only slightly decreased. The mesoporosity created under optimal conditions affects neither the long-range ordering nor the micropore-size.